(untitled) (Research, Society and Development, 2020)
In this work, an electroflotation (EF) method for the treatment of poultry slaughterhouse effluent was proposed, and its efficiency in reducing chemical oxygen demand (COD) was investigated. The following operating conditions were optimized through Doehlert design: [Al2(SO4)3], pH, treatment time, and current density. Treatment of the effluent was carried out in a reactor with TiO2–RuO2 (anode) and iron (cathode) electrodes. The optimum process conditions were obtained with a pH 9, current density of 60 A m–2, electrolysis time of 80 min, and [Al2(SO4)3] of 1.8 mg L–1. Under these operating conditions, turbidity, COD, and biochemical oxygen demand (BOD) removal efficiencies of 93.1%, 80.7%, and 89.7%, respectively, were obtained. The operating cost of the process was calculated at 0.9 USD per m³. The EF method combined with chemical coagulation was shown to be a suitable process for the treatment of effluent from the slaughter and processing of poultry.